How Long Is Too Long: An Individual Time-Window for Motor Planning - Dahan, Anat; Bennet, Rotem; Reiner, Miriam (Frontiers in Human Neuroscience, 2019)
Human motor response time is determined by the matureness of the preceding neural motor preparation process. In the current study, we characterize the optimal temporal boundaries required for the motor preparation process, and its impact on the overall motor response time. In particular, we contrasted short and long preparation durations by measuring the resulting differences in motor response times, in an attempt to find whether an optimal preparation time exists. Using a “Timed Response” paradigm, we presented participants with varying planning intervals prior to a requested motor response, and studied their effect on the timing of initiation of the following movement. We found that, as expected, reaction time shortens as more planning time is provided, yet only until reaching a minimal response time, after which additional preparation time increases the motor response time, thus creating a U-shaped behavioral function. Furthermore, since the minimal response time was found to be an individual characteristic, we suggest that there is an individual optimal time window for motor planning. The existence and personal timing of an optimal timing window can assist in the characterization and medical surveillance of patients with neurological disorders.